(untitled) (Tikrit Journal of Pharmaceutical Sciences, 2023)
This study aimed to determine the frequency of microorganisms isolated from blood samples of patients with septicemia admitted to pediatric protection teaching hospital in Baghdad city, the most frequently isolates were gram+ve cocci (Staphylococcus aureus 7 strian and S.epidermidis 11 strain), followed by, Klebsiella pneumoniae 9 strain, Escherichia coli 5 strain and Enterobacter 2strain. There was a significant difference between Staphylococcus aureus and S.epidermidis in Antibiotic sensitivity P value ≤ 0.05. S. aureus 7 strain were resistant to ampicillin, erythromycin and sensitive to vancomycin, cloxacillin, Gentamicin, Ciprofloxacin While S.epidermidis 11 strain were resistant to ampicillin, gentamicin and sensitive to erythromycin, vancomycin, cloxacillin, Ciprofloxacin